2011
DOI: 10.21836/pem20110102
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of 74 horses with disorders of the oesophagus

Abstract: Retrospective analysis of 74 horses with disorders of the oesophagus 74 cases of horses which had been admitted to the Department of Large Animal Internal Medicine between 2000 and the beginning of 2010, have been analyzed retrospectively. Five of these horses are described in detail. A primary obstruction of the esophagus was diagnosed in 60 horses. The diagnosis based on the inability to pass a nasogastric tube and the treatment of choice was the esophageal lavage technique. Other diseases were esophageal dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…Craig et al (1989) reported that recurrent obstructions are common after esophageal lavage, most probably due to following anatomical complications and this decreases long-term survival rates. But a more favorable prognosis following esophageal lavage for treatment of simple choke in horses was reported by Feige et al (2000) and Breuer et al (2011).…”
Section: Esophageal Obstructionmentioning
confidence: 97%
See 4 more Smart Citations
“…Craig et al (1989) reported that recurrent obstructions are common after esophageal lavage, most probably due to following anatomical complications and this decreases long-term survival rates. But a more favorable prognosis following esophageal lavage for treatment of simple choke in horses was reported by Feige et al (2000) and Breuer et al (2011).…”
Section: Esophageal Obstructionmentioning
confidence: 97%
“…Esophageal obstruction (choke) is the commonest esophageal disorder in the horse (Stick 1987, Knottenbelt et al 1992, Fubini 2002, Breuer et al 2011. The most commonly observed clinical sign in horses with esophageal obstruction is regurgitation.…”
Section: Esophageal Obstructionmentioning
confidence: 99%
See 3 more Smart Citations